2020
DOI: 10.5219/1434
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated food quality management system

Abstract: The high-speed growth in the global population has resulted in a deficit of foods, which has stimulated the development of technologies for planting agricultural products and fattening domestic animals. However, these processes are supplemented in many cases by worsening of the quality of foods and their pollution by foreign substances. To guarantee the proper quality and safety of foodstuffs for health, the International Organization for Standardization developed the standards ISO 9001:2015 and ISO 22000:2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Therefore, such concentration was recommended for the fabrication of sausage meat mixes. Scientific works [34], [35], [36], [37] describe studies using different concentrations of the table and sea salts in the range from 0.5 -1.5%; as a result of similar studies, it was found that such concentrations hurt the organoleptic properties of the finished product. The one more recommendation was to enrich them with iodine, preferably by the extract of laminaria to compensate its deficit, what technique is the best recommended for use [38], [39], [40], [41].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, such concentration was recommended for the fabrication of sausage meat mixes. Scientific works [34], [35], [36], [37] describe studies using different concentrations of the table and sea salts in the range from 0.5 -1.5%; as a result of similar studies, it was found that such concentrations hurt the organoleptic properties of the finished product. The one more recommendation was to enrich them with iodine, preferably by the extract of laminaria to compensate its deficit, what technique is the best recommended for use [38], [39], [40], [41].…”
Section: Resultsmentioning
confidence: 99%
“…In the production of fermented meat products, microorganisms of various taxonomic groups play an extremely important role, namely in the formation of specific taste, aroma, color, and consistency [24]. Both fermentative and spontaneous microflora take part in the components' transformation of meat raw materials during the maturation of such products, and the course of this process depends on the metabolic activity of the strains [25], [26].…”
Section: Antagonistic Activity Of Compositionsmentioning
confidence: 99%
“…Chitosan is one of the most widely used edible coatings due to its biocompatibility, biodegradability, and bioactivity. When applied to fruits, vegetables and berries, chitosan creates a semi-permeable film that protects against the development of fungus diseases and slows down metabolic processes [11]. This edible coating is widely used for post-harvest fresh fruits and vegetables preservation.…”
Section: Introductionmentioning
confidence: 99%